Examination of the effect of melatonin use in Pomeroy method of tubal ligation on ovarian histology in rats - Altungul, A. C.; Kale, A.; Sapmaz, E.; Akpolat, N. (Imr Press, 2012)
Objective: To examine the effects of melatonin use in the unilateral Pomeroy method of tubal ligation on ovarian histology in rats. Setting: Firat University Medical School, Obstetrics and Gynecology Department, Elazig. Material and Method: Thirty adult, female rats of Wistar albino species with regular cycles were randomly allocated to three groups in the estrus phase: G1 (n: 10): The abdomen was opened and closed. G2 (n: 10): The group where the abdomen was opened, and the Pomeroy method of tubal ligation was performed. G3 (n: 10): The group where the abdomen was opened, and Pomeroy method of tubal ligation was performed 15 min after 10 mg/kg/ip melatonin administration. Abdomens of all rats were opened six months later and left oophorectomy was performed. Samples of the left ovary were fixed in formaldehyde. The preparations were stained with hematoxylin eosin, and primordial, primary, secondary and tertiary follicles were counted. All the numbers were added up to determine the ovarian follicle reserve. An atretic follicle count was made. The corpus luteum and corpus albicans were counted, and the number of total corpuses were calculated. Regression of angiogenesis within the corpus luteum was examined. Presence of fibrosis on ovarian stroma was examined. An ordinal scale was formed for the regression of angiogenesis within the corpus luteum and presence of fibrosis (none: 0p, present: 1p, markedly present: 2). Follicle cysts in the ovary were counted. Kruskal Wallis variance analysis was used in the statistical analysis of data; p < 0.05 were considered significant. Results: The comparison between G1 and G3 showed that all values were similar (p > 0.05, Kruskal Wallis variance analysis). When G2 was compared with G1 and G3, regression of angiogenesis in the corpus luteum was found to be significantly lower (p < 0.05, Mann Whitney U test), while atretic follicle count and fibrosis were significantly higher in G2 (p < 0.05, Mann Whitney U test). Conclusion: The Pomeroy method of tubal ligation reduces regression of angiogenesis in the corpus luteum, and increases atretic follicles and fibrosis development. Melatonin use restores these harmful effects. Melatonin can be used to refrain from this negative effect of the Pomeroy method of tubal ligation on the ovary.
Keywords: Melatonin; Ovarian histology; Pomeroy tubal ligation; Rat